Aktivitas Harian Macaca fascicularis di Kawasan Kebun Campuran - Sarti, Yili; Kamilah, Santi Nurul; Jarulis, Jarulis (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2024)
Indonesia is the largest habitat for numerous species of primate, one of them is Macaca fascicularis. This species can live in various habitats, ranging from primary forests to residential areas. One of the habitats where M. fascicularis lives is a mixed garden area in Kepala Curup Village, Binduriang Sub-district, Rejang Lebong Bengkulu, which is adjacent to a residential area. The objective of this study was to observe the daily activities of a group of M. fascicularis in that area. Data were collected from April to June 2020. The sample objects were determined using the focal animal sampling method, which consisted of four individuals: alpha males, adult females, adolescents, and juveniles. Each individual was identified based on their physical characteristics. Data were collected using the continuous-time recording method, with a total observation of 16,800 minutes. The study revealed that M. fascicularis activity in the mixed garden area was highest in feeding (34.36%), followed by moving (26.43%), resting (25.36%), playing (7.20%), grooming (5.61%), vocalizing (0.55%), and conflict (0.50%). No mating activity was observed. The group size of the M. fascicularis in this area was limited (n = 9) and consisted of only one male. All adult females were in the period of lactation, which resulted in a low level of mating activity and conflict within the group AbstrakIndonesia merupakan habitat terbesar dari berbagai jenis primata, termasuk Macaca fascicularis. Primata ini dapat dijumpai pada berbagai tipe habitat, mulai dari hutan primer hingga Kawasan pemukiman penduduk. Salah satunya habitat ditemukannya M. fascicularis adalah di kebun campuran Desa Kepala Curup Kecamatan Binduriang Kabupaten Rejang Lebong yang berbatasan dengan pemukiman penduduk. Tujuan dari penelitian ini adalah untuk mengamati aktivitas harian pada satu kelompok M. fascicularis pada kawasan kebun campuran ini. Pengambilan data dilakukan pada bulan April hingga Juni 2020. Penentuan objek sampel menggunakan metode focal animal sampling, terdiri dari empat individu target yaitu jantan alfa, betina dewasa, remaja dan juvenile. Masing-masing individu telah dikenali berdasarkan ciri fisiknya. Data diambil menggunakan metode continuous time recording dengan total waktu pengamatan 16.800 menit. Dari penelitian yang telah dilakukan diketahui bahwa aktivitas M. fascicularis di kebun campuran tersebut tertinggi pada aktivitas makan (34,36%), kemudian diikuti aktivitas berpindah (26,43%), istirahat (25,36%), bermain (7,20%), grooming (5,61%), bersuara (0,55%), konflik (0,50%). Tidak ditemukan aktivitas kawin. Kelompok ini termasuk kelompok dengan anggota yang sangat sedikit (9 individu), dengan hanya terdapat 1 individu jantan. Semua betina dewasa dalam masa menyusui bayi. Kondisi itu berpengaruh pada rendahnya aktivitas kawin dan konflik di dalam kelompok.